تجليات النمط الأم الأولى في معلقة امرئ القيس - عياش، خالد فريد مصطفى; الديك، إحسان يعقوب (مركز جيل البحث العلمي, 2023)
وجه البحث أنظاره صوب تجليات الأم البدائية في معلقة امرئ القيس، فقد أماط اللثام عن وجهها، وأزاح الستار عن صورها المختلفة، فهي بغية مقدسة، وهي مرضعة أو حبلى، وهي كالظبية، أو البيضة، أو النخلة، فهذه الأم التي تطرق إليها الشاعر، ليست حقيقية من لحم ودم، وإنما كانت الأم الكبرى/ عشتار القابعة في قعر اللاوعي الجمعي المشترك بين الشعوب. The research focussed its attention on the manifestations of the primitive mother in the Mu'allaqah of Imru’ al-Qais. He removed the veil from her face and unveiled her various images. She is a sacred prostitute, and she is breastfeeding or pregnant, and she is like a doe, or an egg, or a palm tree. This mother, whom the poet addressed, is not real, made of flesh and blood, but she was the Great Mother/Ishtar, who resided at the bottom of the common collective unconscious among nations.
Keywords: الشعر الجاهلي -- المعلقات الشعرية -- صورة المرأة